The Most Important Writing Material in Ancient Times: Papyrus - Atılgan, Mehmet (Information World, 2006)
Papyrus was the most important writing material in ancient times. Before papyrus tablets which made of pats and pans, plain stones, cushion, bronz, zinc, cuppor, silver or gold were used to write on. Besides these, writing materials which were made of plant roots and leaves, wooden tablets which were smeared with wax, tablets made of ivory and organic writing materials made of flax stem were used, too. However, none of these were essentials, influential or permanent like papyrus. Papyrus was first used in Ancient Egypt in 3300s BC. Later, spreading over all Mediterranean countries, it became the most popular writing material. Papyrus remained valuable until XI century AD. Papyrus existed in several kind, different colour and several type of quality according to its whiteness, thickness, dimensionand polish. Papyrus used to be sold in different prices according to its praperties such as its lenght, quality etc. Papyrus was called in various names according to its thickness, width, colour and usage. These names reflected papyrus’s quality and price. They also reflected the area they were used. On the papyrus, scientific and literary articles such as mathematical calculations, astronomy, medical texts, magical words, religions texts, lists of kings, list of geographical places, list of cities, course boooks, mytological writings, adventure stories and articles of geography were written. Written papyrus was kept and transferred rolled in boxes and leather cases.
Keywords: Papyrus